Accommodation needs, motivation and market attraction: a conceptual study on accessible tourism industry for people with disabilities in Malaysia - Surendran Balan; Santhi Raghavan (Global Research Review in Business and Economics, 2022)
Tourism sector, specifically accessible tourism, is getting more positive progress in the last few decades. Studies in the past mainly focused on inclusive tourism or tourism for all. Somehow, accessible tourism, which includes people with disabilities, is one of the ignored consideration in the field of tourism development. Most studies have ignored the inclusion of people with disabilities in the tourism sector. Making tourism more accessible to the disabled is not only a social responsibility, but there is a significant economic and business need to improve accessibility as it can boost the attractiveness of tourism in Malaysia. Past evidences show that by making adjustments to facilities, providing accurate and important information, and understanding the needs of people with disabilities can result in increased number of visitors. Thus, the main purpose of the study is to investigate this overlooked segment of our society, in order to come up with recommendations that can influence the intention to travel among people with disabilities in Malaysia. Data will be collected from 100 respondents which includes 50 who are disabled and have traveled more than once and stayed in a hotel for at least one night within last year and 50 participants consisting of managers from different hotels operating in Malaysia by employing semi-structured interviews. These 50 respondents with disabilities include people with mobility and physical impairments and people with hearing and communication disabilities. The data gathered will be investigated by employing two statistical packages, namely SPSS and Smart PLS. Multiple regression analysis will be utilized to predict the value of the variables in this research. (Abstract by authors)